The Pixelated Professor: Faculty in Immersive Virtual Worlds - Blackmon, Stephanie (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
Online environments, particularly virtual worlds, can sometimes complicate issues of self expression. For example, the faculty member who loves punk rock has an opportunity, through hairstyle and attire choices in the virtual world, to share that part of herself with students. However, deciding to share that part of the self can depend on a number of factors: departmental guidelines, ideas of professionalism, privacy concerns, or the need for separation between the in-class self and the out-of-class self. In my study on faculty in virtual worlds, I examined faculty members’ perspectives on recreating and being themselves in immersive virtual environments.